Trudna przestrzeń. O filmie Roberta Stando Strach ma wielkie oczy - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The article analyses and interprets Robert Stando’s little-known educational film Strach ma wielkie oczy [Fear has large eyes]. The film was made in 1965 and produced by the Documentary Film Studio in Warsaw. The author explores the original character of the film, reconstructing the stylistic and compositional techniques used by filmmakers, among others, in the field of cinematography (underwater photography), editing, word function, music, sound effects etc.